1983
DOI: 10.1007/bf01967330
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of salivary secretion by histamine H2-antagonists—a study on the cat submandibular gland

Abstract: The aim of the present work was to establish whether the secretory process can be influenced by histamine H2-receptor antagonists, burimamide and metiamide. These drugs were applied intravenously and the secretion was evoked by the electrical stimulation of the chorda tympani nerve or by carbachol (i.v.). In addition to the measurements of the flow of saliva, the blood flow through the gland was measured in some experiments. Both H2-antagonists significantly reduced the rate of salivary secretion induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…As is shown in the present work, histamine injected intra-arteriaUy into the gland increases salivation which is induced by carbachol infusion. We have shown in the experiments with histamine H2-antagonists, burimamide and cimetidine, that both drugs inhibit salivation of the cat submandibular gland if it is stimulated by the chorda tympani nerve [24]. The histamine H 2-receptors antagonists seem to inhibit histamine effects on the secretory and thereafter on the vascular apparatus of the organ.…”
Section: Discussionmentioning
confidence: 97%
“…As is shown in the present work, histamine injected intra-arteriaUy into the gland increases salivation which is induced by carbachol infusion. We have shown in the experiments with histamine H2-antagonists, burimamide and cimetidine, that both drugs inhibit salivation of the cat submandibular gland if it is stimulated by the chorda tympani nerve [24]. The histamine H 2-receptors antagonists seem to inhibit histamine effects on the secretory and thereafter on the vascular apparatus of the organ.…”
Section: Discussionmentioning
confidence: 97%
“…In rat parotid tissues, histamine is reported to stimulate H2 receptors and induce amylase secretion (Eguchi et al, 1998). Salivary secretion in cats and rats is inhibited by histamine H2 receptor antagonists (Stanovnik and Erjavec, 1983;Sim and Ang, 1985). Adenylyl cyclase-linked G protein-coupled receptor activation serves an important role in salivary protein secretion via intracellular cAMP production (Yamada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that histamine could act as a stimulator of salivary secretion in submandibular gland (SMG) of cats and dogs (Shimizu andTaira 1980, Stanovnik andErjavec 1983). Furthermore, histamine treatment induces the translocation of aquaporin-5, which modulates water secretion to produce primary saliva, to the plasma membrane in human SMG cells (Kim et al 2009).…”
Section: Introductionmentioning
confidence: 97%